On the implementation of cryptoalgorithms based on algebraic graphs over some commutative rings - Kotorowicz, J.S.; Ustimenko, V.A. (Condensed Matter Physics, 2008)
The paper is devoted to computer implementation of some graph based stream ciphers. We compare the time
performance of this new algorithm with fast, but no very secure RC4, and with DES. It turns out that some
of new algorithms are faster than RC4. They satisfy the Madryga requirements, which is unusual for stream
ciphers (like RC4). The software package with new encryption algorithms is ready for the demonstration. Стаття присвячена комп’ютерному застосуванню деяких потокових алгоритмiв шифрування, що базуються на графах. Ми порiвнюємо швидкiсть нового алгоритму з швидким, але не дуже безпечним алгоритмом RC4 та DES. Цi алгоритми задовiльняють вимоги Мадриги, що є нетиповим для потокових алгоритмiв (типу RC4). Пакет комп’ютерних програм на основi нового алгоритму є готовим для демонстрацiї.